Effectiveness of auriculotherapy on anxiety during labor: a randomized clinical trial - Reginaldo Roque Mafetoni; Mariana Haddad Rodrigues; Lia Maristela da Silva Jacob; Antonieta Keiko Kakuda Shimo (Universidade de São Paulo, 2018)
ABSTRACT Objective: to evaluate the effectiveness of auriculotherapy on the anxiety of women during labor. Method: this is a randomized, parallel, triple-blind clinical trial. 102 parturients with gestational age ≥ 37 weeks, cervical dilatation ≥ 4 cm and two or more contractions in 10 min were selected and randomly assigned into three groups to receive auriculotherapy, placebo or control (routine care). Auriculotherapy was applied with crystal microspheres to the shenmen, uterus, neurasthenia area and endocrine points, and anxiety was assessed by the Hamilton Anxiety Rating Scale (HAM-A). Analyzes were performed using the Kruskal-Wallis, Generalized estimating equations, Chi-square and Fisher's exact tests. Results: the groups showed no significant difference at baseline according to the HAM-A. After the intervention there was a significant increase in HAM-A scores at 120 min in the placebo versus auriculotherapy group (mean difference (MD) 3.62, confidence interval (CI) 0.42-6.81, p=0.0265) and control versus auriculotherapy group (MD 4.88, CI 1.87-7.88, p=0.0015). Conclusion: the parturients with auriculotherapy presented lower levels of anxiety according to the HAM-A score after the treatment when compared to the women from the other groups; this can represent alternative care in obstetric practice. Registration: n. RBR-47hhbj.